Epidemiological survey of lentiviruses in small ruminants in western Cariri of Paraíba, Northeast Brazil (Research, Society and Development, 2022)
Small ruminant lentiviruses are present in most countries that have goat farming activities, but in the Brazilian Northeast, where 92.8% of the national herd is concentrated, it is necessary to raise the awareness of breeders and create effective control programs for the virus in herds. The objective of this work was to carry out an epidemiological survey of lentiviruses in small ruminants in the western Cariri region of Paraíba, Northeastern Brazil. Stratified probabilistic sampling was carried out in two stages: in the first, the rural properties were randomly selected, and in the second, also randomly, the animals within the selected properties were selected. On the occasion of the visits, epidemiological questionnaires were applied in order to gather information about the absence or presence of some practices and conditions that act as possible factors associated with the occurrence of the investigated diseases. The serological diagnosis was made with the Immunodiffusion test in Agar Gel (AGID), using a commercial kit. From a sample of 1000 dairy goats, the serum prevalence of 5.90% (59/1000) for LVPR infection (I.C. 95%) was revealed. It was possible to observe that three municipalities (Coxixola, Parari and Serra Branca) had a prevalence of seropositive individuals of 30.51%, 22.03% and 16.95%, respectively. And the other municipalities ranged from 1.69% to 11.86%. In the present research, 80 properties were sampled, 36.25% (29/80) obtained seroreactive animals. At the end of this work, it can be concluded that the Lentivirus infection of small ruminants is present in dairy goats in western Paraiba, where the immediate region of Sumé/PB is located.